Modeling the impact of virtual reality technology integration for snow and ice sports on enhancing regional sports tourism economy - Wang, Ning; Zhao, Ping; Wang, Xing; Wang, Yixuan (Sciendo, 2024)
In order to reveal the relationship between the integration of ice and snow sports virtual reality technology and the regional sports tourism economy, this paper establishes a structural equation model for ice and snow sports VR and sports tourism economy. Determine the latent variables and observed variables in the structural equation model (i.e., questionnaire items), take the online distribution of questionnaires to obtain the research data in this paper, and use the model in this paper to explore and analyze the integration of ice and snow sports virtual reality technology and regional sports tourism economies. The questionnaires developed in this paper meet the standard requirements of the reliability test, and the fitting indexes of the model have reached the state of conformity, as shown by the results. The path coefficients of the latent variable (VR experience quality) to the observed variables (Q11, Q12, Q13, Q14) are 0.555, 0.409, 0.344, and 0.348, respectively, and the non-standard coefficient of the quality of ice and snow sports VR experience (Q1) to the local sports tourism economy (Q4) is 0.941, P<0.05, which confirms that the ice and snow sports VR experience has a positive impact on the local sports tourism economy promotion effect.